Pengembangan Media Komik Menggunakan Aplikasi Android Kodular Pada Materi Sistem Persamaan Linear Tiga Variabel di Kelas X - Riza Sawitri; Rusmining; Windi Aprilia Asidik (Jurnal Pendidikan Matematika Universitas Lampung, 2024)
This study aims to develop a comic media application of the System of Linear Equations in Three Variables, test the validity and practicality of the System of Linear Equations in Three Variables comic media application for class X students of SMKN 3 Yogyakarta. This research uses the Research and Development (R&D) research method with the ADDIE (Analyze, Design, Development, Implementation and Evaluation) type of development model. Data collection techniques with observation, questionnaires and interviews. Data analysis techniques use analysis of the validity and practicality of comic media. The research involved 5 students for small class trials, and 30 students for large class trials The results of the development in the form of media in the form of System of Linear Equations in Three Variables comic media applications. The results of the study obtained an average score of validity of material experts 59 and media experts 76.5 with “Good” criteria. Practicality test with the results of the average score of practicality of small class trials 68.5 and large class trials 65.72 with “Good” criteria. This shows that the System of Linear Equations in Three Variables comic media application meets the valid and practical criteria so that it is considered as an alternative to be used in learning mathematics.